Review of Ice-Induced Scour Impacts to Navigation and Structures - Carr,Meredith L; Dahl,Travis A (2017)
Ice in navigation channels and around structures can cause significant damage that requires expensive repairs. This damage can also trigger delays that have the potential to disrupt the entire navigation system, well beyond the reach of the stretches of water directly impacted by ice. One example is upstream of Melvin Price Lock and Dam where ice-induced scour was repaired at a cost in excess of $1,000,000 and the scour hole reappeared within a year of the repair. Therefore, this report outlines the risks to navigation and structures, including a review of the available literature.